Genetic Diversity and Population Structure of Schima superba From Southern China - Bai, Qingsong; He, Boxiang; Cai, Yanling; Lian, Huiming; Zhang, Qian; Liang, Dongcheng; Wang, Yingli (Frontiers in Ecology and Evolution, 2022)
The tree Schima superba is important for afforestation and fire prevention in southern China. The wood of this tree can also be used for furniture and buildings; however, the lack of genetic background and genomic information for this species has led to reduced speed of wood yield and quality improvement. Here, we aimed to discover genome-wide single nucleotide polymorphisms in 302 S. superba germplasms collected from southern China, and to use these SNPs to investigate population structure. Using genotyping by sequencing, a total of 785 high quality SNP markers (MAF≥0.05) were identified from 302 accessions that collected from seven geographical locations. Population structure analyses and principal coordinate analyses indicated that these germplasm resources can be clearly and definitely separated into different populations. The S. superba accessions originating from Yunnan (YN) and Guangxi (GX) fell into the same population, separate from the accessions originating from Guangdong (GD), which indicated that these two regions should be regarded as major provenances of this species. In addition, two independent core germplasm sets with abundant genetic polymorphisms were constructed to support the breeding work. The identification of SNP markers, analyses of S. superba population genetics, and construction of core germplasm sets will greatly promote the molecular breeding work of S. superba.